The Game of Skittles on the Northern Route of the Camino de Santiago - Rodríguez-Fernández, José E.; Lorenzo-Moledo, Mar; García-Álvarez, Jesús; Míguez-Salina, Gabriela (Frontiers in Psychology, 2020)
The main purpose of this study was to analyze the presence and current situation of the game of skittles throughout the northern route of the Camino de Santiago. Thus, we considered its current practice, modalities, where it is played, and its different manifestations as an informal and formal game (sport), comparing it with other traditional games on this pilgrimage route. To do this, a mixed qualitative-quantitative study was designed with 89 participants (municipal professionals, politicians, players, club managers, and teachers), constituting an informant for each municipality through which the Northern Way passes. An ad hoc questionnaire was used for the data collection, which was processed through content analysis by expert judges (qualitative section) and by using the IBM-SPSS statistical package (version 25). The results of the study show notable skittles activity on the Northern Camino (58.32% of the municipalities), reflected in the number of skittles alleys (n = 291), the number of clubs, associations, and peñas participating in federated leagues (n = 162), and the wide range of varieties of skittles currently active on the Camino (n = 20). The relationship between skittles and local culture, both symbols of identity in these northern Spanish regions, made it possible to preserve the traditional heritage in these places, keeping it alive today, despite the push toward new and more attractive leisure and sport trends.